(untitled) (Revista NUPEART, 2023)
By problematizing the reproduction of colonial power in acting as an art teacher at Cieja Ermelino Matarazzo, a project aimed at basic education for young people and adults offered by the city of São Paulo, I present the possibility of exercising an autoethnogra- phic writing, gestated in the experience as performer member of the Coletivo Parabelo. Through this autoethnographic gesture, I aim to highlight the sexist, racist and patriarchal bases conventio- nally naturalized inside and outside the school context, from the report of a performance class about the Brazilian artist Flávio de Carvalho’s Experience No3 and its reverberations, as a way to trig- ger a process of self-criticism and self-transformation inherent to the praxis of researcher and professor performer.